P–218 Analysis of the occurrence of microbial contamination in IVF culture system and the effect of microorganisms on embryo development and clinical outcomes. (6th August 2021) - Du, F; Li, R; Zhang, Q; Wang, W
Abstract: Study question: what is the source, prevalence, and influence of microbial contamination on in vitro fertilization (IVF) and embryo transfer (ET) cycles? Summary answer: Microbial contamination mainly occurs on Day 2, most caused by Escherichia coli carried with semen. ICSI could prevent contamination effectively and get good clinical outcomes. What is known already: Microbial contamination occurs in IVF-ET system occasionally, which is hard to stop happening. The IVF culture system and laboratory environment, the patients' follicular fluid and semen are not absolutely sterile, while the antibiotics in culture medium isn't effective for all microbe types, and the artificial operations may bring in microbes. Generally, microbial contamination leads to degradation of embryos, reduction the number of embryos available, and infection of female reproductive tract, which would increase the cost of patients' time, money, and bring psychological damages. A better understanding of embryo contamination in IVF culture system is of added value. Study design, size, duration: A total of 29583 IVF-ET cycles were enrolled in this prospective observational study, from January 2010 to December 2020, included 70 microbial contamination cycles discovered in Day1-Day3 (D1-D3) of in vitro culture. Follicular fluid and semen saved on oocyte retrieval day, and culture medium contaminated were examined and identified for microorganisms at each contamination cycle. Participants/materials, setting, methods: Compared the contamination rate of different insemination methods (IVF/ICSI/IVF+ICSI), different in vitro culture days (D1-D3), and different samples examination (follicular fluid, semen, culture medium) respectively, identified the source of microorganism types, compared the IVF culture outcomes and clinical outcomes between total contamination group (TC group, 42 cases) and partial contamination group (PC group, 28 cases). Main results and the role of chance: A total of 70 microbial contamination cases occurred in 29583 oocyte retrieving cycles (0.24%), and it was observed only in IVF embryos but never in ICSI (Intracytoplasmic sperm injection) embryos. 38 contamination cases occurred on D2 with a highest ratio (54.3%) compared to D1 (32.9%) and D3(12.9%); Compared with follicular fluid, semen was the main cause inducing contamination from D1 to D3, and Escherichia coli in semen and culture medium, Enterococcus faecalis in follicular fluid proved to be the most common sources. Compared with TC group, the PC group showed a lower rate of No-available embryos (21.4% vs 81.0%) and a higher rate of blastocyst formation (41.2% vs 28.6%), In addition, the clinical pregnancy rate of PC group was higher than that of TC group in both fresh and frozen-thawed embryo transfer cycles (31.3% vs 16.7%, 38.5% vs 0.0%). Limitations, reasons for caution: Further study is still necessary to better understand the sources that induce microbial contamination embryos, and more efficient methods are required to remove the microbes on these contaminated embryos so as better develop and manage a sterile micro-environment for successful embryo growth. Wider implications of the findings: The differential embryonic microbe types associated to different IVF culture and clinical outcomes in patients undergoing IVF-ET might have profound implications for understanding the microbial sources and making a better management of IVF culture system. Trial registration number: Not applicable